Model of adiabatic nitration of aromatic compounds - Кондратов, Сергей Алексеевич; Красильникова, Анна Александровна (Eastern-European Journal of Enterprise Technologies, 2013)
The article discusses the use of modern computer simulation techniques for the analysis and search of the best variants of an industrial process organization. The main objective of the study is to develop a mathematical model of the adiabatic nitration of aromatic compounds. The use of modern methods of computer simulation for the adiabatic nitration will reduce energy consumption and amount of wastes. The article presents a developed computer simulation model of stationary continuous adiabatic nitration. It permits to describe the process of nitration and removal of excess of heat by distillation of a part of the reaction mass. The properties of the model were studied, the speed of convergence was determined. On the example of the nitration of benzene, it was shown that the process temperature, predicted by the model was close to the data. The results of the research can be applied in practice for the design problems and optimal organization of the process